1986
DOI: 10.1007/bf01273848
|View full text |Cite
|
Sign up to set email alerts
|

Funktionelle Pathomechanismen der Analfissur

Abstract: In a prospective consecutive study of 40 patients with anal fissure we analysed the anal sphincter function at rest and rectal distension. Healthy persons with comparable age and sex distribution were controls. The anal pressures were registered with thin water perfused catheters (2 ml/min). Our patients with anal fissure showed significant elevation of anal pressures at rest along the whole length of anal canal. During rectal distension only the distal part of anal sphincter (up to a level of 2 cm from the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Most studies have demonstrated high resting anal pressure in patients with chronic anal fissure [ 133–135] with at least a short‐term reduction in anal pressure following lateral sphincterotomy [ 136]. Many studies however have failed to show a sustained long‐term reduction in anal hypertonia after this procedure despite clinical fissure healing, suggesting that IAS spasm rather than any functional constitutive hypertonia is more a result rather than a cause of the fissure itself [ 137, 138]. These changes have been coupled with abnormal RAIR in patients with chronic fissures, frequently associated with longer high pressure zone length at rest along with variation in the duration and extent of the inhibitory curve [ 139–142].…”
Section: The Role Of the Ias In Specific Anorectal Diseasementioning
confidence: 99%
“…Most studies have demonstrated high resting anal pressure in patients with chronic anal fissure [ 133–135] with at least a short‐term reduction in anal pressure following lateral sphincterotomy [ 136]. Many studies however have failed to show a sustained long‐term reduction in anal hypertonia after this procedure despite clinical fissure healing, suggesting that IAS spasm rather than any functional constitutive hypertonia is more a result rather than a cause of the fissure itself [ 137, 138]. These changes have been coupled with abnormal RAIR in patients with chronic fissures, frequently associated with longer high pressure zone length at rest along with variation in the duration and extent of the inhibitory curve [ 139–142].…”
Section: The Role Of the Ias In Specific Anorectal Diseasementioning
confidence: 99%
“…Chronische Krankheitsverl~iufe mit Narbenbildungen, sogenannten Vorpostenfalten, hypertrophierten Analpapillen und inkompletten inneren Fisteln sind eine h~iufige Folge [1,2,7,13]. Infolge dieser Schmerzen kommt es zu einer Verkrampfung des Musculus sphincter ani intemus, einer dadurch verursachten Abdrosselung der Blutgeffil3e und somit schlechten Spontanheilung.…”
unclassified